SURFACE SEDIMENT COMPOSITION OF WESTERN COAST OF RUPAT STRAIT RIAU PROVINCE - Wahyu Novra Wanda; Rifardi '; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRAKThe research was conducted in May 2014, in the western part of the Rupat Strait. The aim of study was to determine the sediment material horizontally. This samples were taken using Eckman Grab from 9 sampling points. The analysis of the organic content in the sediment was also done.The results showed that the composition of the sediment in the western part of the Strait Rupat composed of lithogenous (rocks, mica, quartz ) and biogenous ( litter and Foraminifera). Lithogenous composition of rocks dominate waters and existede evenly at each sampling point. The highest percentage found in a location close to the mainland, this was suggested that the materials carried by the tide of Malacca and ebb currents of the Sungai Masjid River piled around this sampling point. In addition, the type of rock could have also come from erosion and anthropogenic activities in water around the edge.The organic matter content of sediment was highest at the sampling point close to the mangrove area. This was due to getting the supplay of organic material from the mangrove areas.Keywords: Composition, Tidal Currents, Sediment, Rupat Strait, Mangrove